Effect of environmental variables on development of Fusarium wilt in chickpea (Cicer arietinum) cultivars - MINA, USHA; DUBEY, S C (The Indian Journal of Agricultural Sciences, 2010)
An experiment was conducted during winter (rabi) season of 2005–07 in laboratory and field to assess influence of environmental parameters on wilt caused by Fusarium oxysporum f. sp. ciceris in ‘Pusa 212’ and ‘BGD 1005’ chickpea (Cicer arietinum) cultivars at IARI, New Delhi. Under controlled laboratory experiments the growth and sporulation of F. oxysporum f. sp. ciceris was observed at different temperatures. The ‘Pusa 212’ showed larger incubation period, less wilt incidence and higher yield in comparison ‘BGD 1005’. Early sowing minimizes wilt incidence in both the cultivars. Lowest mean wilt incidence (22.6–25.5%) and maximum mean grain yield (13.5–14.3 tonnes/ha) were recorded in the crop sown on 10 and 20 November. Similar trend was observed in ‘BGD 1005’ whereas 20 November sown ‘Pusa 212’ crop showed lowest wilt incidence (15.3 and 20.1%) and highest grain yield (16.2 tonnes/ha) during both the years. Maximum and minimum ambient temperature and soil temperature were positively and significantly correlated with wilt incidence in ‘Pusa 212’.